2015
DOI: 10.21608/ejar.2015.155469
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Characteristics of Neem Oils Extracted From Seed, Whole Fruit and Flesh

Abstract: his work aimed to study the chemical composition of fresh neem seed, whole fruit, and flesh and also their defatted meal. Also this study was carried out to investigate the physical and chemical properties (color, taste, odor, status, RI, FFA, PV, k232, IV, SV and unsap.), fatty acids composition, phenol and flavonoid compounds of neem oils extracted by solvent from seed, whole fruit and flesh. The results can be summarized as follows: Neem seed contained a high percentage of crude oil, protein and crude fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Broad-spectrum natural anticancer remedies should be extended through systematic screening of the unexplored wealth of the plant kingdom. The neem plant has attracted the attention of researchers for its potent antioxidant, antimicrobial, and anticancer activities of extracts from different plant parts, including unripe and ripe fruits [ 11 ], whole fruit and flesh [ 12 ], fruit epicarp [ 13 ], leaves [ 14 , 15 , 16 ], flowers and stem bark [ 17 ], and roots [ 18 ]. Corresponding to these studies, the current work also revealed that the methanolic extracts of neem fruit mesocarp and epicarp had significant antiproliferative effects on all tested cell lines (PC-3, MCF-7, and Caco-2) in a dose-dependent manner, with the mesocarp extract being more potent against the three cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broad-spectrum natural anticancer remedies should be extended through systematic screening of the unexplored wealth of the plant kingdom. The neem plant has attracted the attention of researchers for its potent antioxidant, antimicrobial, and anticancer activities of extracts from different plant parts, including unripe and ripe fruits [ 11 ], whole fruit and flesh [ 12 ], fruit epicarp [ 13 ], leaves [ 14 , 15 , 16 ], flowers and stem bark [ 17 ], and roots [ 18 ]. Corresponding to these studies, the current work also revealed that the methanolic extracts of neem fruit mesocarp and epicarp had significant antiproliferative effects on all tested cell lines (PC-3, MCF-7, and Caco-2) in a dose-dependent manner, with the mesocarp extract being more potent against the three cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have determined the antioxidant, antimicrobial, and anticancer potential of neem extracts from different plant parts along with individual compounds commonly present in these extracts [ 10 ]. These include unripe and ripe fruits [ 11 ], whole fruit and flesh [ 12 ], fruit epicarp [ 13 ], leaves [ 14 , 15 , 16 ], flowers and stem bark [ 17 ], and roots [ 18 ]. Manikandan et al [ 19 ] attributed the modulating capabilities of neem leaf extract for cancer cell proliferation and apoptosis to its antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%